2021
DOI: 10.3389/fcimb.2021.691757
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinases: Potential Drug Targets Against Schistosoma japonicum

Abstract: Schistosoma japonicum (S. japonicum) infection can induce serious organ damage and cause schistosomiasis japonica which is mainly prevalent in Asia and currently one of the most seriously neglected tropical diseases. Treatment of schistosomiasis largely depends on the drug praziquantel (PZQ). However, PZQ exhibits low killing efficacy on juvenile worms and the potential emergence of its drug resistance is a continual concern. Protein kinases (PKs) are enzymes that catalyze the phosphorylation of proteins and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 102 publications
(130 reference statements)
0
11
0
Order By: Relevance
“…Moreover, suppressor of cytokine signaling 7 may be involved in the suppression of host immune responses via the inhibition of cytokine-inducible activator of transcription-mediated signal transduction [88,89]. In schistosomes, protein kinase plays essential roles in growth, development, and host interaction; therefore, they have been considered as targets for drugs against parasitic diseases in many research efforts [90]. Serine/threonine protein phosphatases are important for the control of S. japonicum growth and reproduction [81], whereas cullin-3 is a core component of the E3 ubiquitin ligase complex and may play roles in the development of the reproductive organs of S. mekongi [24,91].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, suppressor of cytokine signaling 7 may be involved in the suppression of host immune responses via the inhibition of cytokine-inducible activator of transcription-mediated signal transduction [88,89]. In schistosomes, protein kinase plays essential roles in growth, development, and host interaction; therefore, they have been considered as targets for drugs against parasitic diseases in many research efforts [90]. Serine/threonine protein phosphatases are important for the control of S. japonicum growth and reproduction [81], whereas cullin-3 is a core component of the E3 ubiquitin ligase complex and may play roles in the development of the reproductive organs of S. mekongi [24,91].…”
Section: Plos Onementioning
confidence: 99%
“…Results revealed its essentiality for miracidia viability, schistosomula development and survival, adults pairing, and female maturation [28] . Wu et al [29] claimed in their review that Schistosoma TKs were identified in two types: receptors, and non-receptors (cytosolic TKs). The first included epidermal growth factor receptor (EGFR), a transmembrane glycoprotein, with high tegumental transcriptional expression activity.…”
Section: Protein Kinases (Pks)mentioning
confidence: 99%
“…While SjIR-1 was mainly expressed in the tegument basal membrane and muscles, SjIR-2 was expressed in female vitelline tissue and male parenchyma. Therefore, to develop a safe drug utilizing SjIR inhibitors, it is important to explore their roles in relation to host IRs [29] .…”
Section: Protein Kinases (Pks)mentioning
confidence: 99%
See 2 more Smart Citations